ANALISIS PENGETAHUAN PUBLIK TERHADAP MEDIA DAKWAH RIFQAN TV - Budi Roni Wijaya; Fatikhah Nurrahmi Andina (Universitas Lambung Mangkurat, 2020)
This research was conducted aiming to determine the level of insight and public response in South Kalimantan to Rifqan TV. Rifqan TV transforms its Islamic television propaganda activity into the net streaming, replacing old-brand DakwahSunnahDotCom. This study applies descriptive quantitative survey analysis methods, employing a positivist paradigm. The survey research was conducted on 170 respondents to acquire the general description of South Kalimantan people towards Rifqan TV as a streaming-based Islamic da'wah television. One of the essential criteria of respondents is the loyal user of the previous platform. In this research, nearly half of the respondents watch Rifqan TV and believe that it can substitute the older one. More than half of the respondents know the rebranding activity using social media and recognizes the brand and the logo. Half of the respondents believe that Rifqan TV is worth watching and is well-suited for all ages, notably Millenials. Rifqan TV is considered a source of educational content and a platform for social problem-solving. The ease of access to Rifqan TV pinpoints its brand personality. It also can be reached from various regions, especially within South Kalimantan.